2005
DOI: 10.1002/ijc.21115
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of dietary fiber andLactobacillus casei administration for prevention of colorectal tumors

Abstract: The epidemiologic evidence that dietary fiber protects against colorectal cancer is equivocal. No large-scale clinical study of the administration of Lactobacillus casei has been reported. We examined whether dietary fiber and L. casei prevented the occurrence of colorectal tumors. Subjects were 398 men and women presently free from tumor who had had at least 2 colorectal tumors removed. Subjects were randomly assigned to 4 groups administered wheat bran, L. casei, both or neither. The primary end point was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
161
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(167 citation statements)
references
References 32 publications
1
161
0
5
Order By: Relevance
“…Clinical trials showed that administration of LcS prevented the recurrence of superficial bladder cancer and colorectal tumors. [10][11][12] A communitybased field trial exhibited the efficacy of LcS-containing fermented milk in preventing acute diarrhea caused by enteric pathogens in children. 13 Synbiotic treatment using LcS prevented postoperative infectious complications in biliary cancer surgery.…”
Section: Potent Induction Of Il-12 and Augmentation Of Host Immune Dementioning
confidence: 99%
“…Clinical trials showed that administration of LcS prevented the recurrence of superficial bladder cancer and colorectal tumors. [10][11][12] A communitybased field trial exhibited the efficacy of LcS-containing fermented milk in preventing acute diarrhea caused by enteric pathogens in children. 13 Synbiotic treatment using LcS prevented postoperative infectious complications in biliary cancer surgery.…”
Section: Potent Induction Of Il-12 and Augmentation Of Host Immune Dementioning
confidence: 99%
“…Although the results of systematic and wellcontrolled clinical studies in CRC prevention are not yet available, published reports suggest cautious optimism. [58][59][60] Although our study design does not address causality, it is plausible that curcumin contributes to chemoprevention via expansion of the native Lactobacilli in the context of overall increase of colonic microbiome richness. Similar effects may be ascribed to increased Bifidobacteria, which have also been shown to reduce aberrant crypt foci in mice receiving dimethylhyrazine.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus johnsonii and Lactobacillus casei suppress CRC tumor growth in patients and modulate the intestinal immune response. 110,111 Antibiotics have long been used to eradicate H pylori in the upper GI tract, and treatment is associated with a significant reduction in gastric Another growing area of interest is in modulating the gut microbiota to prevent toxicity associated with the chemotherapy and radiation used to treat cancer. A recent study identified the role of bacterial beta-glucuronidase in mediating GI toxicity of a common drug used for colon cancer CPT-11.…”
Section: Gut Microbiota In Malignancymentioning
confidence: 99%